Pengaruh Efikasi Diri, Persepsi Profesi Guru, dan Lingkungan Keluarga terhadap Minat Menjadi Guru pada Mahasiswa Pendidikan Ekonomi Universitas Bhinneka PGRI Tahun Akademik 2023/2024 - Yohana, Maya Octavia; Umami, Nailariza (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The purpose of this study was to determine the effect of self-efficacy, perceptions of the teaching profession, and family environment on interest in becoming a teacher for economic education students at Bhinneka PGRI University in the 2023/2024 academic year. Correlational quantitative method was used using multiple regression analysis. The population in this study was 181 while the sample taken was 124 respondents. The data collection technique used a questionnaire. The results of the research test show that (1) partially the self-efficacy variable has a positive and significant effect on interest in becoming a teacher (2) partially the variable perception of the teaching profession has a positive and significant effect on interest in becoming a teacher (3) partially the family environment variable has a positive and significant effect on interest in becoming a teacher (4) simultaneously the variables of self-efficacy, perception of the teaching profession, and family environment have a positive and significant effect on interest in becoming a teacher.  Overall, self-efficacy, perceptions of the teaching profession, and the family environment provide an effective contribution of 61.9% to the interest in becoming a teacher. And the remaining 38.1% is influenced by other variables not discussed in this study.